Blended E-learning in the architectural design studio: an experimental model. (18th December 2017) - Mohammed, Mohammed F. M.
Abstract: The availability of information & communication technologies (ICT) has great potential for a surge in E-learning techniques. However, traditional one-on-one tutoring, especially in the field of architecture, represents some sort of an impediment of applying E-learning approaches in the architectural design arena. This piece of research explores experimentally the possibility of integrating some ICT techniques –especially cloud technologies- in an architectural design studio context. It starts by providing a theoretical framework that addresses the theoretical concepts of E-learning, its different mechanisms and techniques, concepts of cloud technology and its applications. This is followed by a presentation of architectural design teaching methodologies, stages and requirements. The researcher introduces a model for exploration. This covers structure, operational definitions, roles of different parties and data analysis techniques. The paper concludes by discussing and evaluating the model in action, and its outputs, hurdles encountered and possible refinements for future consideration. Abstract : The paper introduces a proposed model for applying E-learning approaches in the architectural design arena by using a blended e-learning technique.